Квантовомеханiчний опис фермiонного дублету та його зв’язок з рiвнянням Дiрака - Simulik, V. M.; Krivsky, I. Yu. (Publishing house "Academperiodika", 2018)
A brief review of the diﬀerent ways of the Dirac equation derivation is given. The foundations of the relativistic canonical quantum mechanics of a fermionic doublet on the basis of the Schr¨odinger–Foldy equation of motion are formulated. In our approach, the Dirac equation is derived from the Schr¨ odinger–Foldy equation.